Matrix-analytic methods : (World Scientific, 2002)
Proceedings of the Fourth International Conference, held July 14-16, 2002 in Adelaide, Australia. For Graduate students, academics, researchers, and industry professionals in mathematics modeling, numerical and computational mathematics, probability and statistics, and engineering